The expression (3x² - 6x + 11) - (10x² - 4x + 6) is equivalent to the expression A, expression (-3x² - 5x - 3) - (-10x² - 7x + 2) is equivalent to the expression C, and expression (12x² + 6x - 5) - (5x² + 8x - 12) is equivalent to the expression B.
What is polynomial?
Polynomial is the combination of variables and constants systematically with "n" number of power in ascending or descending order.
[tex]\rm a_1x+a_2x^2+a_3x^3+a_4x^4..........a_nx^n[/tex]
We have a polynomial shown in the picture.
A = -7x² - 2x + 5
B = 7x² - 2x + 7
C = 7x² + 2x - 5
The expression is:
= (3x² - 6x + 11) - (10x² - 4x + 6)
= -7x² - 2x + 5
= A
= (-3x² - 5x - 3) - (-10x² - 7x + 2)
= 7x² + 2x - 5
= C
= (12x² + 6x - 5) - (5x² + 8x - 12)
= 7x² - 2x + 7
= B
Thus, the expression (3x² - 6x + 11) - (10x² - 4x + 6) is equivalent to the expression A, expression (-3x² - 5x - 3) - (-10x² - 7x + 2) is equivalent to the expression C, and expression (12x² + 6x - 5) - (5x² + 8x - 12) is equivalent to the expression B.
Learn more about Polynomial here:
brainly.com/question/17822016
#SPJ5